Exploration of Early Childhood Education Management in Pesantren: A Case Study of Salafiyah Karangpandan Pesantren - Wisudaningsih, Endah Tri; Ghony, Djunaidi; Sutiah, Sutiah (Jurnal Pendidikan Islam, 2024)
Purpose – This research aims to explore the management of early childhood education (PAUD) within the context of pesantren, specifically at the Salafiyah Karangpandan Pesantren in Pasuruan. This study addresses a gap in previous research by focusing on the planning, organization, implementation, and supervision of early childhood education management in a pesantren environment, providing both theoretical and practical insights. Design/methods/approach – This study employs a qualitative case study design to understand the phenomena of PAUD management at Salafiyah Karangpandan Pesantren, Pasuruan Indonesia contextually and empirically. Data were collected through in-depth interviews, participant observations, and document analysis. Participants included caregivers of the pesantren, the headmaster, coordinators, educators, and administrative staff, selected through purposive and snowball sampling techniques. Data were analyzed using an interactive analysis model that encompasses data condensation, data display, and conclusion drawing/verification. Findings – The study found that effective PAUD management in pesantren involves strategic planning focused on the vision of promoting Quranic reading with tartil. An organizational structure based on competence, trust, familial relationships, and welfare creates a productive work environment. Implementation is guided by charismatic leadership and a supportive religious atmosphere, adhering to the Qira’ati system. Supervision through scheduled and conditional evaluations ensures continuous quality improvement. Research implications – These findings highlight the importance of a holistic approach in the management of early childhood education within the pesantren environment, suggesting that effective planning, organization, implementation, and supervision are crucial. This research can serve as a guide for policymakers, educators, and pesantren administrators to enhance PAUD quality by adopting the Qira’ati system and ensuring charismatic leadership.